Conceitos de território e lugar na contemporaneidade: a produção nas teses de pós-graduação em Geografia de 2001-2011 - Fernandes, Mariane de Oliveira (2013)
This dissertation aims to expose and discuss the insights presented in Geography on the concepts - shapes, place and territory in contemporary obtained through the readings and analyzes works by geographers and non - geographers, and also making use of analytical reading in theses produced in Postgraduate courses in Geography in the period 2001-2011. To achieve the purposes of the investigation was turned to survey, selection and collection of information about place and territory, the theses that have these keywords which were defended in those programs Postgraduate using queries to the portals of Coordination improvement of Higher Education Personnel (CAPES), Public Domain, and in the very pages of these programs. The development of research it was considered more appropriate to the purposes of the study using the Historical Method Description, which is to investigate events and processes in order to ascertain the importance and influence they have in contemporary society to better understand their roles in society. The choice of this method considered characteristics of observation, recording, analysis and description, which allows the establishment of relationships and correlations between phenomena in order to discover with accuracy the frequency of occurrence and their relations with other events. When building a reflection on the concepts of place and territory, there were many paths taken by various thinkers foreign and Brazilian, considering the genesis since adopted these concepts to contemporary perspectives of what is conventionally called "contemporary themes of geography." It can be considered that, at present, the current critical renewal of Geography has inserted in studies of new researchers concern with social data, focusing on analyzes involving various approaches political, economic and social inserted and debated in their speeches theses. Also realizes the rescue of theories and concepts used by geography about place and territory. Though dimly, these concepts form are intended to explain the current phenomena and highlight the main theoretical and methodological trends in use of geographic approach in the beginning of XXI century.